2010
DOI: 10.1088/0031-9155/55/24/002
|View full text |Cite
|
Sign up to set email alerts
|

Modeling silicon diode dose response factors for small photon fields

Abstract: The dosimetry of small fields is important for the use of high resolution photon radiotherapy. Silicon diodes yield a high signal from a small detecting volume which makes them suitable for use in small fields and high dose gradients. Unshielded diodes used in large fields are known to give a varying dose response depending on the proportion of low energy scattered photons in the field. Response variations in small fields can be caused by both spectral variations, and disturbances of the local level of lateral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 18 publications
(33 reference statements)
2
29
0
Order By: Relevance
“…The overresponse in small radiation fields of silicon diodes, which incorporate silicon of density 2.3 g/cm 3 and possibly other high‐density material in their sensitive volumes and surroundings, has been well documented 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 38 , 39 , 40 , 41 . Diamond detectors, which have a sensitive volume of density 3.5 g/cm 3 , have been reported to overrespond in small fields 16 , 39 , 41 , 42 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The overresponse in small radiation fields of silicon diodes, which incorporate silicon of density 2.3 g/cm 3 and possibly other high‐density material in their sensitive volumes and surroundings, has been well documented 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 38 , 39 , 40 , 41 . Diamond detectors, which have a sensitive volume of density 3.5 g/cm 3 , have been reported to overrespond in small fields 16 , 39 , 41 , 42 .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported on the response of ionization chambers, diodes, and the microdiamond 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 detector in small radiation fields for flattened beams, using either experiment or Monte Carlo simulations. Where necessary, small field correction factors false(kQclinQmsrfclin,fmsrfalse), as defined by Alfonso et al, (18) have been provided.…”
Section: Introductionmentioning
confidence: 99%
“…39,40 The accuracy of a planning system depends on the accuracy of commissioning data, which are either unavailable or inaccurate for fields smaller than 2 cm due to the lack of electron equilibrium, volume averaging, and spectral variation. 41,42 Plans with a larger numbers of small fields are more susceptible to the leaf end and tongue-andgroove effects, which were not included in the study but can be modeled using a stair function. 43 It is worth pointing out that although a simple level reduction method was used in the study for fluence stratification and MLC sequencing, the fluence regularization method was F.…”
Section: Number Of Aperturesmentioning
confidence: 99%
“…These detectors were chosen for this study because they have both been shown to perform well for output factor determination for field sizes down to 1 × 1 cm 2 for 6 MV photons in flat beams from the Varian Clinac. [21][22][23] All the profile and the PDD measurements were performed at a source to surface distance (SSD) of 100 cm. The transverse profiles were measured at depths of 2.5, 5, 10, 20, and 30 cm.…”
Section: A1 Water Phantom Measurementmentioning
confidence: 99%